Sosialisasi Penggunaan Media Pembelajaran E-Learning Berbasis Model Problem Based Learning Dalam Meningkatkan Motivasi Belajar Dan Hasil Belajar Peserta Didik Di MA Putra Al-Islahuddiny Kediri Kabupaten Lombok Barat - Ulfah Nurkhaeroni; Ripaiyah (Universitas Mataram, 2022)
Education is a very fundamental need for everyone until the end of his life. Education is a form of learning, with education we gain knowledge and skills both individually and in groups. E-learning media is the basis for the development of information and communication technology. This learning model involves students as a whole in solving a real problem, PBL is a contextual approach, which is student-centered. With PBL this can increase curiosity. The purpose of this study was to determine the effect of e-learning media based on problem based learning models in increasing students' motivation and learning outcomes at MA Putra Al-Islahuddiny Kediri. The method used starts from planning to the final stage, namely the conclusion. Based on a learning motivation questionnaire from twenty aspects of the statement, the highest in statement six is ​​88% and the lowest is in the nineteen aspect, which is 60%. The learning outcomes before using e-learning media based on problem based learning models had an average value of 75%, but after using e-learning media based on problem based learning models there was an increase in learning outcomes, namely 85%. So that students can be motivated in learning to use e-learning media based on problem based learning so that there is an increase in learning outcomes.